Models for Evaluating the Quality of Public Services and Their Application- Case of DOST Agency - Yusifova, Rubaba; Badalov, Badal; Huseynli, Rahman (ADA University, 2025)
This study investigates the absence of systematic performance evaluation tools at Azerbaijan’s DOST Agency—an innovative, citizen-centric institution delivering social welfare and labor services. Although DOST has achieved high citizen satisfaction ratings and digital integration, it lacks formal mechanisms to assess service quality beyond output indicators. Using a qualitative case study approach, the research draws on a semi-structured expert interview and a comprehensive review of international evaluation models—SERVQUAL, Citizen Report Cards (CRC), the Balanced Scorecard (BSC), and ISO 9001. The study proposes a hybrid evaluation framework tailored to DOST’s operational realities and governance environment, combining citizen-centric feedback instruments with internal performance monitoring and quality assurance systems. Findings highlight that while SERVQUAL and CRC can capture citizen perceptions and trust, internal data integration through BSC and process standardization via ISO 9001 are essential for institutional sustainability. The research contributes both practically—by offering a scalable roadmap for performance evaluation—and theoretically, by adapting global models to post-Soviet service governance contexts. The proposed hybrid approach enhances transparency, trust, and decision-making capacity within the DOST Agency, aligning it more closely with Azerbaijan’s strategic public administration reforms.
Keywords: Azerbaijan -- Public administration -- Evaluation.; Social welfare administration -- Evaluation.; Public sector reform -- Post-Soviet states.; Public services -- Quality control.; Performance evaluation -- Government agencies.